Perlindungan Hukum Terhadap Pembeli Atas Kelalaian yang Dilakukan oleh PPAT dalam Jual Beli Tanah Warisan - Delia Mariyanti; Saidin Saidin; Zaidar Zaidar (Universitas Medan Area, 2021)
Land Deed Making Officials (henceforth referred to as PPAT) is the public official who is authorized to make authentic deeds concerning certain legal action regarding land or property rights over flat units. PPAT is demanded to work carefully, thoroughly and responsibly because the PPAT deed is used as evidence for the transfer of land rights. When PPAT is negligent in making the deed then it may result in loss for others. As in the Supreme Court verdict No.156K/Pdt/2020, where PPAT has been negligent in making the deed and resulted loss experienced by the buyer due to the loss payment and the land he had purchased. Even though the buyer has made sale and purchase clearly before the PPAT, that PPAT deed should be able to provide legal certainty. Therefore, this research is trying to analyze and answer the problems on to what extend is the legal accountability of PPAT when the sale and purchase deed of inherited land that made before him is cancelled by the Supreme Court, to what extend is the legal protection for buyer against the negligence committed by PPAT in making the sale and purchase deed of inherited land that has not been divided and whether judge’s decision in the Supreme Court verdict No.156K/Pdt/2020 has accommodated protection for the buyer.